2011
DOI: 10.1590/s1984-29612011000200010
|View full text |Cite
|
Sign up to set email alerts
|

Strategic control of cattle ticks: milk producers' perceptions

Abstract: In order to evaluate milk producers' knowledge about tests on tick sensitivity to acaricides, efficiency tests and strategic control, questionnaires were delivered to 670 producers. From these, 163 responses were received. These producers had sent ingurgitated female ticks to be subjected to tests on tick sensitivity to acaricides at Embrapa between 2001 and 2005. Most of the completed questionnaires came from the State of Minas Gerais, Brazil. After descriptive analysis and correlation of variables, it was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
0
10
1
5
Order By: Relevance
“…Among the interviewees, another 27% responded that they would only change the product when it stopped working. This proportion was lower than what was found by Amaral et al (2011a) (54.4%), Vivas et al (2006a) (54.1%) and Rocha et al (2006) (64%), who also found that declining efficiency was the main reason for changing the product.…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…Among the interviewees, another 27% responded that they would only change the product when it stopped working. This proportion was lower than what was found by Amaral et al (2011a) (54.4%), Vivas et al (2006a) (54.1%) and Rocha et al (2006) (64%), who also found that declining efficiency was the main reason for changing the product.…”
Section: Resultscontrasting
confidence: 68%
“…This situation seems to have worsened, because Amaral et al (2011a) observed the same situation among 84.2% of the producers who were using tick sensitivity tests carried out by EMBRAPA Dairy Cattle, mostly in the southeastern region (91%). Three percent of the owners said that they used any acaricide that was commercially available ( Table 2).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, the questionnaires were constructed, the interview processes were conducted and the subsequent descriptive analyses of the data and description of the results were carried out in accordance with social research methodology (MINAYO, 1993;GIL, 1991), using questionnaires validated by Rocha et al (2006Rocha et al ( , 2011a and Amaral et al (2011).…”
Section: Data Gatheringmentioning
confidence: 99%
“…Based on this situation, it has been recommended that strategic tick control should be implemented (MARTINS et al, 2006). However, milk producers continue to undertake tick control without using any technical criteria and with a high frequency of treatments (ROCHA, et al, 2006(ROCHA, et al, , 2011bAMARAL et al, 2011). Moreover, they use subjective parameters for applying and using acaricides (LEITE; ROCHA, 1999).…”
Section: Introductionmentioning
confidence: 99%